Pengaruh Menghafal Al-Qur’an Terhadap Kecerdasan Emosional Siswa - Rofiq, Ainur; Khoirinnada, Niken Ayu (Ngaos: Jurnal Pendidikan dan Pembelajaran, 2024)
This research aims to determine how memorising the Al-Qur'an affects the emotional intelligence of class VIII students at SMP BP Amanatul Ummah Pacet Mojokerto. The research uses a quantitative approach with an associative type of research. The population is all 395 class VIII students. A sample of 79 students was taken by random sampling. Data was collected by questionnaire and analysed using simple linear regression. The research results show (1) There is a positive and significant influence between memorising the Qur'an and emotional intelligence as shown by the regression equation Y=51.744+0.416X, t value > t table (2.730 > 1.990), and a significance value of 0.010 ( <0.05), (2) The coefficient of determination (R2) of 0.184 shows that the contribution of memorising the Qur'an to emotional intelligence is 18.4% and other factors influence the remainder, (3) The more routine you memorise the Qur'an, increasing students' emotional intelligence. Recommendations for further research include considering other variables influencing emotional intelligence, expanding the research subjects and locations, conducting qualitative research, and comparative studies between groups who routinely and non-routinely memorise the Koran.